2018
DOI: 10.1007/s42242-018-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the success of intramuscular gluteal injections and its impact in psychiatry

Abstract: There are 12 billion injections given worldwide every year. For many injections, the intramuscular route is favoured over the subcutaneous route due to the increased vascularity of muscle tissue and the corresponding increase in the bioavailability of drugs when administered intramuscularly. This paper is a review of the variables that affect the success of intramuscular injections and the implications that these success rates have in psychiatry and general medicine. Studies have shown that the success rates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 43 publications
1
46
1
4
Order By: Relevance
“…3,16,17 In addition, several studies have found a significantly low rate of IM injection success ranging from 32% to 52% using CT scan or ultrasound for non-antipsychotic drugs. [38][39][40][41] Variables associated with an increased rate of IM injection failure included obesity, site of injection, subcutaneous fat depth, female sex, and nurse experience levels. [38][39][40][41] The inadvertent administration of an IM injection within the SQ tissue may result in subtherapeutic drug concentrations, slower absorption rate, localized tissue damage, and reduced drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,16,17 In addition, several studies have found a significantly low rate of IM injection success ranging from 32% to 52% using CT scan or ultrasound for non-antipsychotic drugs. [38][39][40][41] Variables associated with an increased rate of IM injection failure included obesity, site of injection, subcutaneous fat depth, female sex, and nurse experience levels. [38][39][40][41] The inadvertent administration of an IM injection within the SQ tissue may result in subtherapeutic drug concentrations, slower absorption rate, localized tissue damage, and reduced drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] Variables associated with an increased rate of IM injection failure included obesity, site of injection, subcutaneous fat depth, female sex, and nurse experience levels. [38][39][40][41] The inadvertent administration of an IM injection within the SQ tissue may result in subtherapeutic drug concentrations, slower absorption rate, localized tissue damage, and reduced drug efficacy. 38 The delivery of risperidone through SQ injection may, therefore, be advantageous for obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome will be that the inexpensive and realistic IM simulation will provide nursing students with a tool that they can utilize to practice this necessary skill, so they are better prepared for when they enter the clinical setting. 1 1 1…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there is high demand for continued innovation, and the spread of new technologies remains relatively unrestrained in many countries [4]. Advanced emerging technologies, such as three-dimensional bioprinting, which can be used to print large tissue structures, auto-injection devices, which can eliminate the use of needles, or new kind of prosthetics are already reaching a stage of preclinical and clinical research [5,6,19]. These new technologies can impact a range of healthcare problems, and it will be their 'market pull', as well as the regulations around them, that are likely to be the key factors defining their potential success going forward [7,8].…”
Section: Introductionmentioning
confidence: 99%